Non-Governmental Organization Struggle in Nigerian Democratic System - Adekunle, Ahmed Oluwatobi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
Democracy is fundamental to any nation's growth, stability, and harmony. Nigeria's path to democratic governance has been complex and challenging, marked by corruption, military interventions, and persistent political instability. In this context, non-governmental organizations (NGOs) have emerged as vital actors in promoting social justice, human rights, and good governance. This study evaluates the role and struggles of NGOs within Nigeria's democratic system, with a specific focus on Ilorin metropolis in Kwara State. Using a survey research design and a sample size of 155 respondents determined through Taro Yamane's formula, the study gathered data from residents to assess perceptions of NGO effectiveness and engagement. Findings reveal that NGOs must proactively engage policymakers and governmental institutions to influence policy formulation and implementation. However, a minority of respondents (10) strongly disagreed with the proposition that increased funding from government and international donors is necessary for NGOs to function effectively. The study recommends enhanced collaboration between NGOs and public officials to strengthen democratic governance through improved communication, policy advocacy, and institutional partnerships.